Autoimmune Encephalitis With Multiple Autoantibodies: A Diagnostic and Therapeutic Challenge. Issue 2 (March 2018) - Kim, Albert E.; Kang, Peter; Bucelli, Robert C.; Ferguson, Cole J.; Schmidt, Robert E.; Varadhachary, Arun S.; Day, Gregory S.
Abstract : Introduction: Indications for autoantibody testing in patients with rapid-onset cognitive impairment have expanded in step with the growing number of disease-associated autoantibodies and clinical syndromes. Although increased access to autoantibody testing has broadened our understanding of the spectrum of autoimmune encephalitis (AE), it has also produced new challenges associated with deciphering the contributions of disease-associated autoantibodies in patients with atypical clinical features and/or multiple autoantibodies. These challenges are illustrated through presentation of a patient with AE associated with autoantibodies against intracellular and cell-surface neuronal antigens. The implications of detection of multiple autoantibodies are considered in the context of relevant literature, and used to frame a diagnostic and therapeutic approach. Case Report: A previously well 67-year-old man presented with encephalopathy and psychosis, impaired visual fixation, and ataxia, emerging over 3 months. Hu, CRMP-5, and NMDAR autoantibodies were identified in the cerebrospinal fluid. No malignancy was discovered despite extensive investigations. An aggressive course of immunotherapy temporarily stabilized his course; however, the patient succumbed to his illness 10 months after symptom onset. Lack of sustained response to immunotherapy and neuropathologic findings suggested that AE associated with Hu antibodies was primarily responsible for this patient's progressive decline. Conclusions: Multiple autoantibodies may be detected in patients with AE. When antibodies targeting intracellular and cell-surface antigens are detected together, investigation and treatment of syndromes associated with intracellular antibodies should be prioritized, acknowledging the link between these antibodies and irreversible neuronal injury. In paraneoplastic cases, prognosis may be tied to early detection and treatment of the underlying malignancy. Abstract : Supplemental Digital Content is available in the text.